UKURAN PERUSAHAAN, PROFITABILITAS, DAN NILAI PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Abdulah Rakhman; Liauw Bun Fa; Hafizah Rifiyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
The value of the company is very important for shareholders to gain profits in the complexity of their shares. Many fundamental factors can increase firm value and this study aims to determine the effect of firm size and profitability on firm value. The object of research is consumer goods companies listed on the Indonesia Stock Exchange during the 2015-2017 period. The sampling technique used is a non-probability sampling technique with a purposive sampling approach. The research uses a data pooling test, classical assumption test, and hypothesis testing using SPSS 20 and SmartPLS 3. The results show that firm size has a positive effect on firm value and profitability has a positive influence on firm value. Based on the results of this study, it can be concluded that company size and profitability have a positive effect on the value of consumer goods companies. Keywords: firm value, firm size, profitability, consumer goods